Computation of the weakly relativistic plasma dispersion functions using superasymptotic and hyperasymptotic expansions - Pavlov, S.S.; Castejón, F.; Tereshchenko, M. (Національний науковий центр «Харківський фізико-технічний інститут» НАН України, 2010)
A new method to compute the weakly relativistic plasma dispersion functions for complex argument is presented. It is demonstrated that Jacobi fractions represent those functions asymptotically for z→ ∞ in the upper semi-plane.